UPAYA MENINGKATKAN HASIL BELAJAR FISIKA DENGAN MENGGUNAKAN METODE QUANTUM TEACHING DI SMA NEGERI 3 BANDA ACEH - Sri Suryawati (JURNAL FISIKA EDUKASI, 2015)
The purpose of this research is (1) to determine the presence / absence of improving student learning outcomes by using quantum teaching the material straight motion with velocity and constant acceleration, (2) to describe the activities of teachers and students during learning using quantum teaching and (3) to know the students' response to learning using quantum teaching method. This study uses classroom action research (PTK). Subjects were students of X-Mia-4 SMAN 3 Banda Aceh totaling 32 people. Analysis of data using techniques percentage. Based on the results of data analysis can be summarized as follows: (a) an increase in student achievement in the learning process by using quantum teaching method. The use of quantum teaching method can improve learning outcomes in the form of scoring after the replay is held every cycle, both for individual students and the value of the average value of the class. The increase in the average value of such class of cycle 1: value - average student 3.0, and cycle to increase to 2: 3.69. So the average - average increase in value of class X-Mia-4 of the second cycle is of 69%; (B) Activities of teachers and students during the learning process has reflected the ongoing implementation of quantum teaching method in the material straight motion with constant velocity and acceleration. It can be seen from the increase in the activity of students in solving problems, work in teams, and ask questions / express ideas, and (c) The response of students is very positive which is characterized by increasing the percentage of students' response to the use of methods of quantum teaching, which can be seen students happy to study of quantum teaching method. Most students SMA Negeri 3 Banda Aceh said he was happy to learning using quantum methods of teaching the material straight motion with constant velocity and acceleration.